2015
DOI: 10.1186/s41038-015-0009-5
|View full text |Cite
|
Sign up to set email alerts
|

Interpretation for practice guidelines for prevention, diagnosis, and treatment of ventilator-associated pneumonia in burn patients by american burn association

Abstract: “American Burn Association Practice Guidelines for Prevention, Diagnosis, and Treatment of Ventilator-Associated Pneumonia in Burn Patients” was published to provide recommendation for the prevention, diagnosis, and treatment of ventilator-associated pneumonia in burn patients. This article makes interpretations and conclusions for prevention, diagnosis and treatment from this guideline in the combination of domestic burn patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…At present, VAP preventive measures for the above risk factors have been carried out, such as considering Non Invasive Positive Pressure Ventilation (NIPPV) in some types of respiratory failure, spontaneous breathing trial and daily awakening trial to reduce mechanical ventilation time and hospitalization time; Head of bed elevation to 30–45 degrees, reducing unnecessary sputum suction and reducing the replacement of ventilatory circuit to reduce aspiration; Selective decontamination of the digestive tract and selective oropharyngeal decontamination to reduce the colonization of drug-resistant bacteria (Vazquez Guillamet and Kollef, 2018). For burn patients, fluid infusion should be limited to reduce infection (Luo and Guo, 2015). Although studies have shown that long-term prophylactic use of antibiotics can lead to changes in pathogen resistance, other studies have confirmed that early (<7 days) empirical use of antibiotics in ICU can reduce the incidence of VAP (Dahyot-Fizelier et al, 2018; Evans et al, 2018).…”
Section: Prevention Of Vapmentioning
confidence: 99%
“…At present, VAP preventive measures for the above risk factors have been carried out, such as considering Non Invasive Positive Pressure Ventilation (NIPPV) in some types of respiratory failure, spontaneous breathing trial and daily awakening trial to reduce mechanical ventilation time and hospitalization time; Head of bed elevation to 30–45 degrees, reducing unnecessary sputum suction and reducing the replacement of ventilatory circuit to reduce aspiration; Selective decontamination of the digestive tract and selective oropharyngeal decontamination to reduce the colonization of drug-resistant bacteria (Vazquez Guillamet and Kollef, 2018). For burn patients, fluid infusion should be limited to reduce infection (Luo and Guo, 2015). Although studies have shown that long-term prophylactic use of antibiotics can lead to changes in pathogen resistance, other studies have confirmed that early (<7 days) empirical use of antibiotics in ICU can reduce the incidence of VAP (Dahyot-Fizelier et al, 2018; Evans et al, 2018).…”
Section: Prevention Of Vapmentioning
confidence: 99%